Inggris - Lelen Aprilia Dian Putri (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The design and manufacture of this media aims to produce learning media use of an animation-based oscilloscope with a level of validity and practicality that meets the requirements. The design of this learning media uses the ADDIE (Analysis Design Development Implementation Evaluation) model. The ADDIE model has five stages, 1) analysis; 2) design; 3) development; 4) implementation; 5) evaluation. The validity test of the designed learning media consists of two validation stages, 1) the validity of the material experts, tested by two material experts; 2) the validity of media experts, tested by two media experts. The practicality test was carried out by two Audio Video Engineering teachers at SMKN 1 West Sumatra and 12 X TAV 1 students at SMKN 1 West Sumatra. The results of the analysis of the validity of the material with an average score of 0.93 which are categorized as very high and the results of the analysis of media validity with an average score of 0.89 which are categorized as very high. The results of practicality by teachers and students show that the average scores are 94.3% and 80.0%, respectively, which are categorized as very practical. The data obtained shows that the learning media using an animation-based oscilloscope produced is very valid and very practical.